Taxation and Corporate Performance of Quoted Oil and Gas Companies in Nigeria - Abdullahi, Sani Rufai; Ude, Alexandar Onyebuchi; Ekpa, Felix; Ahuoiza , Rahanatu; Sadiq, Hajarat (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
While taxation is claimed to be an indispensable means of revenue generation for the government to meet the expectations of its citizens in terms of the provision of social amenities, it is a means of spending from profits for corporate organisations, which will inevitably have a negligible effect on their profits. In line with the need to appraise how taxation influences corporate profitability, this study evaluates the influence of taxation on the corporate performance of 9 Oil and Gas companies quoted in Nigeria from 2008 to 2022. The analysis was based on random-effect regression as specified by the Breusch-Pagan Lagrangian Multiplier test. The findings reveal that companies’ income tax has a significant negative influence on corporate performance, whereas value-added tax has a significant positive influence on the corporate performance of the sampled Oil and Gas companies. This study recommends that company income tax should be strictly administered in line with ‘the ability to pay’ theory. This is because of the negative influence on the financial performance of the companies. Furthermore, companies should faithfully remit proceeds of value-added tax to the tax authority since it enhances their financial performance.